Uneven distribution of mating type alleles in Iranian populations of Cercospora beticola, the causal agent of Cercospora leaf spot disease of sugar beet - BAKHSHI, Mounes; ARZANLOU, Mahdi; BABAI-AHARI, Asadollah (Phytopathologia Mediterranea, 2011)
<!– [if gte mso 9]> Normal 0 14 false false false IT ZH-TW X-NONE MicrosoftInternetExplorer4 <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –><!–[endif]–> Cercospora beticola, the causal agent of Cercospora leaf spot disease on sugar beet, is thought to be exclusively asexual because no teleomorph has yet been found. The possibility of a clandestine sexual cycle in the Iranian population of Cercospora beticola was evaluated by analyzing the distribution and frequency of the mating type alleles on a microspatial and a macrogeographical scale. A total of 89 single-conidial Cercospora beticola isolates were obtained from sugar beet fields in the Moghan, the Talesh and the Khoy regions. The isolates were identifed using a Cercospora beticola-specifc primer set in a PCR assay. A multiplex PCR method using previously designed mating type primers was used to study the distribution and the frequency of the mating type alleles. All isolates showed either the 805-bp fragment or the 442-bp fragment of the MAT1-1 and MAT1-2 genes, but no isolate had both fragments. The distribution of the mating type genes in the sampled areas was uneven. From three sugar beet fields sampled in the Moghan region, two fields had only MAT1-1 isolates; while in the third field all isolates had only the MAT1-2 allele. In the Talesh region only MAT1-1 isolates occurred, and in the Khoy region the mating type alleles were uniformly distributed amongst the isolates. The skewed distribution of mating type alleles in Northwestern Iran was in line with the lack of a sexual cycle for this species and may also indicate that sugar fields in the Moghan region were infected by C. beticola populations of different origins. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi; –> <!–[endif]–>